2011
DOI: 10.1002/adfm.201101606
|View full text |Cite
|
Sign up to set email alerts
|

High‐Mobility Air‐Stable Solution‐Shear‐Processed n‐Channel Organic Transistors Based on Core‐Chlorinated Naphthalene Diimides

Abstract: High charge carrier mobility solution‐processed n‐channel organic thin‐film transistors (OTFTs) based on core‐chlorinated naphthalene tetracarboxylic diimides (NDIs) with fluoroalkyl chains are demonstrated. These OTFTs were prepared through a solution shearing method. Core‐chlorination of NDIs not only increases the electron mobilities of OTFTs, but also enhances their air stability, since the chlorination in the NDI core lowers the lowest unoccupied molecular orbital (LUMO) levels. The air‐stability of dichl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 42 publications
(74 reference statements)
0
67
0
Order By: Relevance
“…[6,7] One particular target is the development of soluble n-type materials with high device performance. [8][9][10] This is highly desirable for the formation of high-performance complementary circuits composed of p-and n-channel TFTs having similar performance [11] and for the realization of low manufacturing costs in real terms using solution processes, which is one of the greatest potential benefits of organic semiconductors. [12] Perylene tetracarboxylic acid diimides (PTCDIs) are among the most promising n-channel candidates for organic TFTs because of their high electron affinity and large π-orbital overlap in the solid state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] One particular target is the development of soluble n-type materials with high device performance. [8][9][10] This is highly desirable for the formation of high-performance complementary circuits composed of p-and n-channel TFTs having similar performance [11] and for the realization of low manufacturing costs in real terms using solution processes, which is one of the greatest potential benefits of organic semiconductors. [12] Perylene tetracarboxylic acid diimides (PTCDIs) are among the most promising n-channel candidates for organic TFTs because of their high electron affinity and large π-orbital overlap in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…However, naphthalene tetracarboxylic acid diimide (NTCDI) is an analog of PTCDI that has a reduced -electron system compared with that of PTCDI, and has received increasing attention as a building block for soluble n-type organic semiconductors. [8,[20][21][22][23][24][25] Molecules coupled with a rigid -electron core and alkyl chains frequently exhibit thermotropic liquid crystalline mesophases. Furthermore, molecules move easier in liquid crystal phases than in solid phases because of higher fluidity.…”
Section: Introductionmentioning
confidence: 99%
“…80 Bao and coworkers investigated the charge transport properties of some molecular OSCs and found that thin films prepared by solvent-shearing have improved orientation of the molecules with short interplanar distances, resulting in higher n-type mobilities compared to devices fabricated using drop-casting or spin-coating. [81][82][83] The influence of device geometry on the type and amplitude of charge carrier mobilities and especially the stability of the n-channel transport were reported by several research groups. 84 Better performance of top-gated devices is frequently observed and rationalized by easier injection of charges from the source-drain electrodes as the larger active electrode area reduces contact resistance.…”
mentioning
confidence: 99%
“…In recent years, our group as well as others reported a significant number of naphthalene diimide (NDI)-based thin film transistor studies demonstrating excellent and stable n-channel operation even in air that can be attributed to a large electron affinity and close p-stacking [30][31][32][33][34][35][36] . For NDI small molecules, the highest mobilities could be obtained for thin-film transistors of DI-DTYM2 (3.5 cm 2 V À 1 s À 1 ) 34 and for single-crystal transistors of Cl 2 -NDI (8.6 cm 2 V À 1 s À 1 ) 35 , respectively, under ambient operation.…”
mentioning
confidence: 99%